Determinants of Myanmar's trade pattern and policy implications for effective financing - Yuzana Hlaing; Jinhwan Oh; Kyungmin Park (Global Business & Finance Review (GBFR), 2021)
Purpose: This study examines Myanmar's international trade pattern in terms of suggesting strategies to accelerate the country's economic growth. Design/methodology/approach: This study uses a panel dataset of Myanmar's 85 trading partners covering a period of a 25-year period (1994-2018). An empirical analysis based on the gravity model is conducted. Findings: T he empirical results are basically consistent with the prediction of the gravity model, and ASEAN+6 turns out to be the most effective economic bloc among regional dummies. Further comparison between Myanmar's actual and predicted trade flows showed its economic contact with neighboring countries was under-represented. Research limitations/implications: It is recommended for Myanmar to promote regional economic cooperation with neighboring South Asian and ASEAN members based on the perspective that regional competitiveness is in line with national competitiveness. Originality/value: Given the current military coup and potential economic sanctions from the international community, this study is timely and expected to have significant contributions to the literature.
Keywords: 650; Trade Pattern; Myanmar; Gravity Model; Panel Data Analysis